Optimizing Early Childhood Growth and Development through Health Screening, Dental Examination, and Interest-Talent Counseling: KKN-T UMSIDA Community Service Work Program in Pangkemiri Village : Optimalisasi Tumbuh Kembang Anak Usia Dini melalui Skrining Kesehatan, Pemeriksaan Gigi, dan Penyuluhan Minat-Bakat: Program Kerja Pengabdian Masyarakat KKN-T UMSIDA di Desa Pangkemiri - Aditama, Prima; Anjani, Adelia Rahma; Pratama, Alnesta Aurandhi Setya; Devi, Anintya Kurnia; Ardelia, Bella Putri; Baskoro, Deny Indra; Anandita , Eka; Adelia, Erine Hilda; Putri , Fara Nadhirah; Sandria, Feri; Pramono, Marsha Panca Suwita; Ghofur, Achmad Abdul; Dwikisaputra, Revaldo Ananda; Tillah, Rikhlah Qonita; Mubarokah, Umi Chabibah Siti; Anra, Yuana Veby (Indonesian Journal of Cultural and Community Development, 2025)
The 2025 KKN-T Program Group 4 Pangkemiri Village carries the theme "Optimizing Early Childhood Growth and Development" through health screening activities, dental examinations, and psychological counseling related to the recognition of children's interests and talents. This activity was carried out at Aisyiyah Bustanul Athfal 3 Pangkemiri Kindergarten and Baiturrohim Mosque by involving medical personnel, psychologists, teachers, and parents. The results of the activity showed that around 15% of children had nutritional problems and 40% of children had dental problems, so follow-up in the form of referrals and education was needed. In addition, psychology counseling helps parents and teachers understand the importance of recognizing children's potential from an early age. The evaluation of the activity showed an increase in the awareness of parents (85%) and children (70%) towards physical and psychological health. Overall, this program has succeeded in providing real benefits and emphasizing the importance of cross-sector collaboration in supporting children's growth and development holistically. Highlights: 15% of children had nutritional issues, 40% had dental problems → follow-up needed. Counseling improved parents’ and teachers’ understanding of children’s potential. Awareness increased: parents (85%) and children (70%) on health and development. Keywords: Child growth and development, health screening, dental examination, interests and talents, KKN-T, Pangkemiri Village.